Hakikat Pendidik dalam Strategi Pembelajaran - Adelia Putri; Fatimah Zahara; Gusmaneli Gusmaneli (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
Allah has chosen humans as world leaders because of their abilities in various sciences and sciences. They can undertake education to teach and be taught. This differentiates between humans. and other people. Teachers or educators are a very important component of education. Teachers or educators are professional jobs that cannot be carried out by an agency without special conditions that support the implementation of the job. They. must have good character, extensive knowledge and knowledge, competence and qualifications as an educator. Therefore, becoming a teacher or educator is not as easy as we imagine. Their job is not only to transfer knowledge and knowledge to students but also to educate, guide and empower them to become successful people.